Pengaruh Pemahaman Pendidikan Agama Islam terhadap Pengamalan Keagamaan Siswa Sekolah Menengah Atas Negeri 1 Sangkulirang - Nurhandayani, Sri (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
This research in the wake of the fact that in this time, students who study Islamic religious education but in himself has not formed Muslim personality, Beginning of dress, speech, association, and other things. In fact, there are still many who have not established conduct religious teachings such as prayer, fasting, and in her social morals less reflects a Muslim student. And do not rule out some that have very broad spiritual experience can leave worship and even do things that are religiously forbidden.This research aimed to determine whether there is the effect of understanding islamic education on spiritual experience SMA N 1 Sangkulirang. The hypothesis of this study is